Cardiovascular and sympathetic responses to a mental stress task in young patients with hypertension and/or obesity - Garafova, A; Penesova, A; Cizmarova, E; Marko, A; Vlcek, M; Jezova, D (Physiological research, 2014)
Present study was aimed to investigate sympathetic responses to mental stress with hypothesis that the presence of obesity in patients with hypertension has a modifying effect. Young male subjects, 8 with hypertension grade I, with BMI 25 kg/m(2) (HT), 10 with hypertension grade I, and BMI 30 kg/m(2) (HT OB), 14 healthy controls with BMI 30 kg/m(2) (OB), and 13 healthy controls with BMI 25 kg/m(2) (C) underwent the Stroop test. ECG was recorded continuously to evaluate heart rate variability (HRV). Blood pressure (BP) and catecholamine concentrations were measured at baseline, at the end of mental stress test and 15 min thereafter. Patients with HT demonstrated increased adrenaline concentrations and enhanced stress-induced noradrenaline release compared to that in healthy controls. In obese subjects, stress-induced increase of systolicBP was lower compared to lean individuals. Stress exposure induced a significant rise in the low frequency power component of HRV, however the increase was lower in the HT OB group compared to C. Obesity in patients with hypertension did not lead to a different reaction in comparison with lean hypertensive subjects. The present data demonstrate higher sympathoadrenal activity in early-stage of hypertension. Obesity is connected with higher resting systolicBP and modifies the HRV response to mental stress.
Keywords: obezita; Humans; Epinephrine; Case-Control Studies; Electrocardiography; Hypertension; studie případů a kontrol; mladý dospělý; dospělí; Heart Rate; Cardiovascular System; sympatický nervový systém; lidé; kardiovaskulární systém; Stress, Psychological; Adult; krevní tlak; Male; srdeční frekvence; adrenalin; hypertenze; Adolescent; psychický stres; Young Adult; Obesity; mužské pohlaví; Sympathetic Nervous System; Blood Pressure; mladiství; elektrokardiografie